2022
DOI: 10.1063/5.0099142
|View full text |Cite
|
Sign up to set email alerts
|

A near-field study of VO2/(100)TiO2 film and its crack-induced strain relief

Abstract: Temperature-induced metal–insulator transition (MIT) in vanadium dioxide (VO2) has been under intense research interest for decades both theoretically and experimentally. Due to the complex nature of electron correlations, the underlying physics behind the MIT in VO2 has yet to be fully grasped. In this work, we utilize the fine resolution of the scattering-type scanning near-field optical microscope to investigate the MIT in an epitaxial VO2 thin film on the (100)R TiO2 substrate with mid-infrared light. Bidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
0
4
2
Order By: Relevance
“…Note that there were a few recent s-SNOM works in nanocracks in VO 2 films. 49 , 50 However, contrary to our study, they reported a reduction of optical conductivity near the nanocrack region, which was attributed to changes in the metal-insulator transition in the local region. 49 , 50 …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Note that there were a few recent s-SNOM works in nanocracks in VO 2 films. 49 , 50 However, contrary to our study, they reported a reduction of optical conductivity near the nanocrack region, which was attributed to changes in the metal-insulator transition in the local region. 49 , 50 …”
Section: Discussioncontrasting
confidence: 99%
“…Ordinary optical methods using far-field light can be used as a nondestructive and noncontact sampling method, but their probing size is limited to the micron size range due to the diffraction limit (Figure S1). Note that there were a few recent s-SNOM works in nanocracks in VO 2 films. , However, contrary to our study, they reported a reduction of optical conductivity near the nanocrack region, which was attributed to changes in the metal-insulator transition in the local region. , …”
Section: Discussioncontrasting
confidence: 99%
“…The 8 nm thick VO 2 exhibits a sharp IMT behavior and T c of ∼292 K, whereas the 15 nm thick VO 2 shows a gradual and multistep IMT with a T c of ∼313 K. The multistep behavior with a higher T c is attributed to the microcracks on the VO 2 surface. 17,20,22,25,30 Figure 2b,c shows topographic AFM observations. The 8 nm thick VO 2 film has a rather smooth surface with a root mean square roughness (R rms ) of 0.25 nm (Figure 2b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This higher local resistance disturbs the current flow homogeneity and eventually results in an uncontrolled IMT behavior as well as deterioration of stability. These behaviors limit practical optoelectronic applications of VO 2 . For example, in the case of smart window applications, a thicker VO 2 layer is required to maintain a significant transmittance change; however, due to the crack effects, this is incompatible with the stable phase transition behavior with room temperature T c .…”
Section: Introductionmentioning
confidence: 99%
“…These cracks have been reported to be thermally induced -when the sample cools down through the transition temperature, the cracks develop as a means of strain relaxation. [43,44,58] We also show the overview of the cross-section made at 45°t o the previous lamella in Figure 8c, where we see the cracks at a skew angle as our viewing axis is now [100]/]010] with the c-axis being the vertical direction in the images. Observing the structures around the cracks, we notice different sets of orientations from the inset FFTs of Figure 8d,e.…”
Section: Vo 2 On Tio 2 (001)mentioning
confidence: 95%